Exploring the Factors Influencing the Acceptance of IoT Applications in Food Packaging - Konstantinos Rotsios; Dimitris Folinas; Chrysoula Mouchtari; Artemis Andreou; Thomas Fotiadis; Maria-Theodora Folina; Antonios Gasteratos (Foods)
This study explores the transformative role of IoT in enhancing efficiency across the food value chain. It combines secondary and primary research to identify factors that influence IoT adoption in the food sector. A thematic–bibliometric analysis (2010–2024) highlights key themes related to IoT use in the industry, particularly in food packaging and supply chain optimization. The primary research, based on 162 questionnaires, examines factors influencing IoT adoption, such as perceived usefulness, ease of use, self-efficacy, and personal innovativeness. Results show that IoT awareness strengthens the impact of personal innovativeness on attitudes toward IoT. Additionally, a positive attitude significantly influences the intention to use IoT. These findings underline IoT’s potential to enhance efficiency, reduce waste, and positively impact the food industry, emphasizing the importance of increasing awareness to foster its adoption.